2007
DOI: 10.1111/j.1365-2966.2007.12233.x
|View full text |Cite
|
Sign up to set email alerts
|

A signature of the donor star in the extra-galactic X-ray binary LMC X−2

Abstract: Two nights of phase‐resolved medium‐resolution Very Large Telescope spectroscopy of the extra‐galactic low‐mass X‐ray binary LMC X−2 have revealed a 0.32 ± 0.02 d spectroscopic period in the radial velocity curve of the He iiλ4686 emission line that we interpret as the orbital period. However, similar to previous findings, this radial velocity curve shows a longer term variation that is most likely due to the presence of a precessing accretion disc in LMC X−2. This is strengthened by He iiλ4686 Doppler maps th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…MS 1603.6+2600 has P orb ∼ 1.85 h and LMC X‐2 has P orb ∼ 8.16 h (Liu et al 2007), and as LMXBs with P orb < 1 d, they are not expected to produce warped accretion discs (OD01). However, with q ∼ 0.14 for LMC X‐2 (Cornelisse et al 2007), tidal disc precession is likely. MS 1603.6+2600, also known as UW CrB, has a short P orb and likely shares properties with the other short‐period systems, such as having a q < 0.25, making tidal disc precession likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS 1603.6+2600 has P orb ∼ 1.85 h and LMC X‐2 has P orb ∼ 8.16 h (Liu et al 2007), and as LMXBs with P orb < 1 d, they are not expected to produce warped accretion discs (OD01). However, with q ∼ 0.14 for LMC X‐2 (Cornelisse et al 2007), tidal disc precession is likely. MS 1603.6+2600, also known as UW CrB, has a short P orb and likely shares properties with the other short‐period systems, such as having a q < 0.25, making tidal disc precession likely.…”
Section: Discussionmentioning
confidence: 99%
“…MS 1603.6+2600 has P orb ∼1.85 hours and LMC X-2 has P orb ∼8.16 hours (Liu, van Paradijs & van den Heuvel 2007) and as LMXBs with P orb <1 d, they are not expected to produce warped accretion discs (OD01). However, with q ∼0.14 for LMC X-2 (Cornelisse et al 2007), tidal disc precession is likely. MS 1603.6+2600 a.k.a.…”
Section: Lmc X-2 and Ms 16036+2600 (Fig19 And 20)mentioning
confidence: 99%
“…It is also extremely bright for a NS XB, ∼0.5-2 L Edd where L Edd is the Eddington limit. It has a known counterpart, and a mass ratio ≤0.4 (Cornelisse et al 2007).…”
Section: 6mentioning
confidence: 99%
“…This can be explained by the different star formation history of the two galaxies since LMXBs are associated with an older stellar population than HMXBs (Liu et al 2005). LMC X-2 is a binary of period 8h (Cornelisse et al 2007), similar in many respects to Sco X-1. A monitoring has indicated that, during the bright X-ray states, the optical lightcurve lags 20s behind the X-ray lightcurve (McGowan et al 2003).…”
Section: Lmxbsmentioning
confidence: 99%
“…LMC X-2 is a binary of period 8 h (Cornelisse et al 2007), similar in many respects to Sco X-1. A monitoring has indicated that, during the bright X-ray states, the optical lightcurve lags 20 s behind the X-ray lightcurve (McGowan et al 2003).…”
Section: Lmxbsmentioning
confidence: 99%